E-LKPD Model Pembelajaran Discovery Berbasis STEM untuk Meningkatkan Berpikir Kritis - Cahayani, Devita Mika; Istikomah, Dhian Arista; Jana, Padrul; Kintoko, Kintoko (Indo-MathEdu Intellectuals Journal, 2025)
Advances in technology and science require students to adapt to various aspects of life, especially in the field of education. One of the abilities that needs to be improved in 21st century learning is the ability to think critically. This study aims to develop and test the validity of the Electronic Student Worksheet (E-LKPD) of the STEM-based discovery learning model to improve students' critical thinking skills. The development model used is the ADDIE model, which includes five stages: analysis, design, development, implementation, and evaluation. The data analysis technique used is descriptive. The results of the validity test by material experts and media experts show that the E-LKPD developed has a very high validity with an average score percentage of 82%. Based on these results, E-LKPD is considered very valid for use in learning